2018
DOI: 10.1007/s10661-017-6440-2
|View full text |Cite
|
Sign up to set email alerts
|

Tools for monitoring aquatic environments to identify anthropic effects

Abstract: Anthropic activities are directly related to the contamination of aquatic ecosystems owing to the release of numerous chemicals from agricultural and urban waste. These contaminants cause environmental degradation and a decrease in the availability of water quality. The objective of this search was to evaluate the efficiency of physicochemical, chemical, and microbiological tests; extraction of chlorophyll a; and genetic parameters to identify anthropic activities and weather condition effects on the stream wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…Untreated wastewater discharges are the main source of surface water pollution in urban areas [7][8][9][10]. They reduce the quality of the water body and stimulate the proliferation of pathogenic organisms that can cause severe diseases concerning public health [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Untreated wastewater discharges are the main source of surface water pollution in urban areas [7][8][9][10]. They reduce the quality of the water body and stimulate the proliferation of pathogenic organisms that can cause severe diseases concerning public health [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities are related to the contamination of aquatic ecosystems by the discharge of various chemical products from rural and urban activities. These products generate problems in the environment and a decrease in the availability of quality water [2], [6], [7].…”
Section: A Anthropic Activitiesmentioning
confidence: 99%
“…Previous studies have demonstrated metal concentrations, particularly Iron (Fe), in the rivers of the Ivinhema River sub-basin exceeding the threshold defined by the National Legislation Conama 357 of 2005 (Souza, 2007;Kottwitz, 2012;Gonçalves, 2013;Dourado et al, 2017;Maceda et al, 2015;Da Rocha et al, 2018;Dalla Costa and Roche, 2020;Dos Santos et al, 2020;Viana et al, 2020). Metal enrichment in aquatic environments, even those considered essential for the maintenance of life, such as Fe, can cause toxicity, representing environmental risks to local biodiversity and compromising human health through the consumption of contaminated water and fish (Sang et al, 2019;Kortei et al, 2020;Yu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%